Evaluating air quality in China based on daily data: Application of integer data envelopment analysis - Zhou, Z.; Guo, Xiumei; Wu, H.; Yu, J. (Elsevier, 2018)
After high speed development on economics during the past decades, China have accumulated a lot of air environment problems. A lot of studies based on data envelopment analysis (DEA) have been done to measure China's air problem by using monthly or annual data. As the development of real-time air quality monitoring, more valuable daily data should be utilized to evaluate air problem. The present paper constructs a set of DEA models for calculating air quality, in which the integral and zero-sum gain constraints are considered to match the characteristics of daily air monitoring data. An empirical analysis have been done to measure the air quality of 31 main cities in China by using the daily Air Quality Index. There are two main finds as follows. Firstly, all the 31 major cities in China need to do more work to improve air quality, while there are significant differences between the performance of different cities. Secondly, the air quality of Chinese cities has changed over month, the best air quality appeared in August and September while the worst occurred in December and January. Also, we calculate the target values for improving the air quality of Chinese cities.